Characterization of wrinkle morphologies by surface waviness evaluation method during deep forming of multilayer composite preforms. (15th February 2023) - Shen, Hao; Yao, Liting; Legrand, Xavier; Wang, Peng
Highlights: Analysis of surface waviness was proposed to characterize and evaluate the wrinkling in deep stamping of multilayered composite preforms. Surface waviness depends on the fabric architecture, the fabrics with ± 45° fibre orientation and through-the-thickness tufting yarn decrease the wrinkle amplitude by 44–52 %. Three regions with different wrinkling characteristics can be distinguished during forming, the tetrahedral forming shows an important wrinkle-free ratio, up to 50%. Wrinkles can be classified as amplitude-dominated and curvature-dominated, which lead to different optimization methods according to the functional requirements of the products. Abstract: Wrinkling is a common defect in the deep forming of quasi-isotropic composite preforms. The wrinkle morphologies on these double-curved component surfaces have not been clarified thoroughly due to the lack of characterization method. This paper proposes a new method of characterizing wrinkles by assessing the surface waviness. A non-contact measurement based on the structure-from-motion technique is applied for capturing the surface profile. By using Gaussian filter, the waviness profiles are obtained by removal of the irregularities and the form errors. Wrinkle morphology is then defined with the help of the waviness parameters. The results reveal the use of ± 45° fiber orientation on the top layer of fabrics can reduce the average wrinkle amplitude by 44 % and the average wrinkle curvature by 79 %. The tufting yarns in the thickness direction also contribute to decreasing wrinkle amplitude prominently. The wrinkle-free, wrinkle-growing and wrinkle-stable regions can be distinguished in all forming cases, but the proportion of each region varies with component geometry. When the wrinkles need to be partially tolerated in consideration of manufacturing cost, the acceptance-rejection criteria need to be established with the help of waviness parameters.